Spliceosome-Mediated Trans-Splicing: The Therapeutic Cut and Paste - Wally, Verena; Murauer, Eva M.; Bauer, Johann W. (Journal of investigative dermatology, 2012)
Spliceosome-mediated RNA trans-splicing (SMaRT) is an RNA-based technology to reprogram genes for diagnostic and therapeutic purposes. For the correction of genetic diseases, SMaRT offers several advantages over traditional gene-replacement strategies. SMaRT protocols have recently been used for in vitro phenotypic correction of a variety of genetic disorders, ranging from epidermolysis bullosa to neurodegenerative diseases. In vivo studies are currently bringing trans-splicing RNA therapy toward clinical application. In this review, we summarize the progress made toward the medical use of SMaRT and provide an outlook on its upcoming applications.